2018
DOI: 10.7717/peerj.5262
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of bias in morphological identification of carnivore scats confirmed with molecular scatology in north-eastern Himalayan region of Pakistan

Abstract: Scats are often used to study ecological parameters of carnivore species. However, field identification of carnivore scats, based on their morphological characteristics, becomes difficult if many carnivore species are distributed in the same area. We assessed error rates in morphological identification of five sympatric carnivores’ scats in north-eastern Himalayan region of Pakistan during 2013–2017. A sample of 149 scats were subjected to molecular identification using fecal DNA. We used a confusion matrix to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 49 publications
0
20
0
1
Order By: Relevance
“…Similarly, Harrington et al (2010) found that 75 scats identified as mink by experienced field surveyors actually belonged to pine marten (Martes martes), fox, otter, polecat or stoat (Mustela erminea) using DNA barcoding. Scat misidentification can lead to inclusion of prey species consumed by non-focal predators and omission of prey species consumed by the focal predator(s) in dietary assessments, which could have detrimental implications for species conservation and/or management (Martínez-Gutiérrez et al 2015;Akrim et al 2018). Therefore, DNA barcoding (Davison et al 2002;Harrington et al 2010;Shehzad et al 2012aShehzad et al , 2012bAkrim et al 2018) or DNA metabarcoding (Berry et al 2017;Forin-Wiart et al 2018) should be used to identify scats where possible.…”
Section: Predator Assignmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Harrington et al (2010) found that 75 scats identified as mink by experienced field surveyors actually belonged to pine marten (Martes martes), fox, otter, polecat or stoat (Mustela erminea) using DNA barcoding. Scat misidentification can lead to inclusion of prey species consumed by non-focal predators and omission of prey species consumed by the focal predator(s) in dietary assessments, which could have detrimental implications for species conservation and/or management (Martínez-Gutiérrez et al 2015;Akrim et al 2018). Therefore, DNA barcoding (Davison et al 2002;Harrington et al 2010;Shehzad et al 2012aShehzad et al , 2012bAkrim et al 2018) or DNA metabarcoding (Berry et al 2017;Forin-Wiart et al 2018) should be used to identify scats where possible.…”
Section: Predator Assignmentmentioning
confidence: 99%
“…However, morphological faecal analysis can be time-consuming and accuracy hinges on possessing the neces-sary expertise to identify both the predator and its prey (Pompanon et al 2012;Martínez-Gutiérrez et al 2015;Traugott et al 2020). Carnivore scats can be misidentified during field collection, with especially high error rates for sympatric species with morphologically-similar scats and low density carnivores whose scats are sparse (Davison et al 2002;Akrim et al 2018). Prey detection from predator faeces may be influenced by differential digestion of soft-bodied and hard-bodied prey, and variable gut transition times for different prey components (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The study area experiences four different seasons during the calendar year including summer (May-July), autumn (August-October), winter (November-January) and spring (February-April). Major wildlife species in the park include common leopard Panthera pardus, rhesus monkey Macaca mulatta, Asiatic jackal Canis aureus, Kashmir hill fox Vulpes vulpes grifithii, small Indian mongoose Herpestes javanicus, Indian grey mongoose Herpestes edwardsii, barking deer Muntiacus muntjak, Indian pangolin Manis crassicaudata and kaleej pheasant Lophura leucomelanos (Akrim et al 2017(Akrim et al , 2018.…”
Section: Study Areamentioning
confidence: 99%
“…Scat analysis has been used extensively by various researchers in various parts of the world for investigating the diet composition of carnivores, especially the elusive species. However, the correct identification of scats in the field, based on morphology of the scats, is vital otherwise wrong information may be communicated to readers (Akrim et al 2018). Therefore, more recently, field identified scats of carnivores are being subjected to molecular identification techniques for confirmation of the carnivore species.…”
mentioning
confidence: 99%
“…However, morphological faecal analysis can be time-consuming, and accuracy hinges on possessing the necessary expertise to identify both the predator and its prey (Pompanon et al 2012; Martínez-Gutiérrez et al 2015; Traugott et al 2020). Carnivore scats can be misidentified during field collection, with especially high error rates for sympatric species with morphologically similar scats and low density carnivores whose scats are sparse (Davison et al 2002; Akrim et al 2018). Prey detection from predator faeces may be influenced by differential digestion of soft-bodied and hard-bodied prey, and variable gut transition times for different prey components (e.g.…”
Section: Introductionmentioning
confidence: 99%